Willingness to Take Risk: The Role of Risk Conception and Optimism - Thomas Dohmen; Simone Quercia; Jana Willrodt (Institute of Labor Economics (IZA), 2018)
We show that the disposition to focus on favorable or unfavorable outcomes of risky situations affects willingness to take risk as measured by the general risk question. We demonstrate that this disposition, which we call risk conception, is strongly associated with optimism, a stable facet of personality and that it predicts real-life risk taking. The general risk question captures this disposition alongside pure risk preference. This enlightens why the general risk question is a better predictor of behavior under risk across different domains than measures of pure risk preference. Our results also rationalize why risk taking is related to optimism.
Keywords: D91; C91; D81; D01; 330; risk taking behavior; optimism; preference measures; risk conception